2022
DOI: 10.1055/s-0042-1751101
|View full text |Cite
|
Sign up to set email alerts
|

Study to the Effect of Involutional Blepharoptosis Surgery Using Objective and Subjective Parameters

Abstract: Background We investigate the effect of involutional blepharoptosis (IB) surgery based on dry eye symptoms by analysis using objective and subjective measures. Methods We recorded various parameters from patients that underwent levator advancement surgery for IB, totaling 125 eyes (total 65 patients, 5 unilateral, 60 bilateral). Subjective assessment comprised a questionnaire on dry eye-related quality of life score (DEQS), a summary score calculated from DEQS, and six-grade evaluation, the patient's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…SPK is known to mainly occur below the cornea after BP surgery. Asamura et al 6 reported that postoperative MRD-1 should be less than 3 mm because of the possible appearance of SPK due to BP surgery. In this study, SPK area and density scores were found to increase when the MRD-1 increase was more than 2.5 mm with surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SPK is known to mainly occur below the cornea after BP surgery. Asamura et al 6 reported that postoperative MRD-1 should be less than 3 mm because of the possible appearance of SPK due to BP surgery. In this study, SPK area and density scores were found to increase when the MRD-1 increase was more than 2.5 mm with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The condition for SPK worsens, resulting in patient complaints. 3 6 20 21 BP surgery in elderly people must therefore be considered to be a very delicate procedure. There have been no previous reports of a scale evaluation method for SPK by surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study conducted on patients with symptomatic scores and TBUT values indicating dry eye disease before involutional ptosis surgery, improvement was found in symptom scores and TBUT values at 6 months postoperatively ( 18 ). It could be suggested that the initial dry eye symptom status might influence changes in postoperative dry eye scores, a notion supported by the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although the presence and exacerbation of SPK is well known to surgeons involved in IB surgery, the exact cause of SPK has not been fully investigated. 3 Upper lid wiper epitheliopathy (LWE) and superior limbic keratoconjunctivitis (SLK) are the most common causes of upper SPK, while inferior conjunctivochalasis (CCh) and dry eye are the most common causes of lower SPK. 4 Dry eye and lagophthalmos have been extensively studied, 5,6 but the role of friction-related diseases, such as LWE, SLK, and CCh, has been underexplored.…”
mentioning
confidence: 99%